Petatah Petitih sebagai Pedoman Etika dalam Hukum Adat - Harmaini, Harmaini; Supeno, Supeno; Sari, Fitri Kartika; Kusaimah, Kusaimah; Antoni, Elsa (Universitas Batanghari Jambi, 2024)
This research examines the role of petatah petitih, or traditional proverbs, in the context of customary law from a legal philosophy perspective. Deeply embedded in Jambi Malay traditions, petatah petitih serve as moral and legal guidelines passed down through generations. Unlike formal legal systems, petatah petitih function as informal norms that regulate social behavior and resolve conflicts. This study explores how these proverbs reflect the relationship between law, morality, and social harmony within the community. As non-coercive legal principles, petatah petitih convey cultural values that promote justice, respect, and responsibility among individuals. The research also highlights the pedagogical value of petatah petitih in transmitting cultural wisdom, educating younger generations about community norms, and preserving traditional legal systems. Furthermore, the study addresses the relevance of these proverbs in modern times, especially in the face of social change, emphasizing their role in maintaining cultural identity and continuity.